2011
DOI: 10.1002/sia.3838
|View full text |Cite
|
Sign up to set email alerts
|

XPS and SEM study of calcite bearing rock powders in the case of reactivity measurement with HCl solution

Abstract: The dissolution of seven natural limestones and calcareous rocks in hydrochloric acid solution was examined to investigate their capability for wet flue gas desulphurisation. All samples were crushed, ground and sieved to a size-fraction of 150-250 mm. Thereafter they were subjected to a dissolution experiment utilising stepwise titration with hydrochloric acid. The dissolution rates of three calcareous rocks were found to be controlled by reaction kinetics, while the limestones showed mass transfer control. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 22 publications
(52 reference statements)
3
39
0
Order By: Relevance
“…Using the interpretations of Järvinen et al, [24] it is suggested that mass transfer is not the rate determining step in the dissolution reaction since for all samples, the mass transfer coefficient is estimated to be higher than the kinetic rate coefficient.…”
Section: Nitrogen Physisorptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using the interpretations of Järvinen et al, [24] it is suggested that mass transfer is not the rate determining step in the dissolution reaction since for all samples, the mass transfer coefficient is estimated to be higher than the kinetic rate coefficient.…”
Section: Nitrogen Physisorptionmentioning
confidence: 99%
“…Straight lines have been fitted with least squares method for evaluation of the rates of change of pH. The used mathematical model was originally presented by Ahlbeck et al [30,31] and later described by Järvinen et al [24] According to the model, the rate of change in hydrogen ion concentration is given by…”
Section: Nitrogen Physisorptionmentioning
confidence: 99%
See 3 more Smart Citations